Obesity and Overweight among Employees of Medical Technical Institute/ Baghdad - Huda Baqer (Iraqi National Journal of Nursing Specialties, 2023)
Objecti١e: Obesity and overweight are well known risk factors for coronary artery disease, and areexpected to be increasing all over the world. Therefore, we designed this study with the objective todetermine the prevalence of obesity and overweight among the employees of the medical technicalinstitute Baghdad Iraq.Methodology: ٨ cross-sectional study was conducted in the medical technical institute Baghdad Iraq,between January 2006 and march 2006. The enrolled subjects were a convenient sample of employeesof teaching staff, technicians, administrative and labors.Two hundred and three subjects constituted thestudy sample.Results: The final total number of members included in the study was 203, comprising 53 males and150 females. The mean age was 41.9629.47 years. The mean BMl was 27.36=4.86. The prevalence ofoverweight and grade 2 obesity among the studied sample was 50(24.60%), and 92(45.3%)respectively, while no one had gradej obesity.There was significant association between the age of thestudied sample and the BMI grades (020.006) between the educational level and the increase in BMI(1-.009), between the type of employment and the increase in BMI (P=.O18), between positive familyhistory and obesity (p=.ooo), between practicing exercise and the increase in weight.The prevalence of overweight and obesity was high, and more than two thirds of both malesand females were either overweight or obese, which are well known risk factors for many medicaldisorders .Recommendation: The findings of this study indicates that even medical and health staff w ere in needfor a prevention program to tackle the problems of obesity among adult.